103k views
2 votes
Mily wrote the equation −3x=−2x−6

User ToddeTV
by
5.7k points

2 Answers

2 votes

Answer: x=6

Explanation:

You have to get X on one side so you have to either add 2X to both sides or 3X to both sides depending on which one you would rather do and then you get 1X equals -6 and to get X by itself you have to divide by -1 which leaves you with -6 divided by -1 which equals 6

User Nithish Thomas
by
4.9k points
1 vote

Answer:

x=6

Explanation:

-3x=-2x-6

-3x+2x=-6

-x=-6

x=6

User Suhrob
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.